Striped-tailed Yellow-finch nesting success in abandoned mining pits from central Brazilian cerrado - DT. Gressler; MÂ. Marini (Brazilian Journal of Biology)
Suitability of degraded areas as breeding habitats can be tested through assessment of nest predation rates. In this study we estimated nest success in relation to several potential predictors of nest survival in the Stripe-tailed Yellow-finch (Sicalis citrina) breeding in abandoned mining pits at Brasília National Park. We monitored 73 nests during the 2007-breeding season. Predation was the main cause of nest failure (n = 48, 66%); while six nests were abandoned (8%) and 19 nests produced young (26%). Mayfield’s daily survival rates and nest success were 0.94 and 23%, respectively. Our results from nest survival models on program MARK indicated that daily survival rates increase linearly towards the end of the breeding season and decrease as nests aged. None of the nest individual covariates we tested - nest height, nest size, nest substrate, and edge effect - were important predictors of nest survival; however, nests placed on the most common plant tended to have higher survival probabilities. Also, there was no observer effect on daily survival rates. Our study suggests that abandoned mining pits may be suitable alternative breeding habitats for Striped-tailed Yellow-finches since nest survival rates were similar to other studies in the central cerrado region.